Superabsorbent polymer composition and method for preparing same
By using a combination of persimmon extract, glycine and chelating agent in the superabsorbent polymer, and forming a surface crosslinking layer in combination with heat treatment, the problem of insufficient deodorization performance of superabsorbent polymers in the prior art is solved, and excellent deodorization effect is achieved.
Patent Information
- Application Number
- CN202380053061.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-23
- Filing Date
- 2023-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
The existing superabsorbent polymers have problems with insufficient deodorization performance in sanitary materials, especially when the pulp content is reduced or the use of pulp is not used, and it is difficult to effectively inhibit the odor in the liquid and the odor caused by bacterial growth.
By controlling the combination and mixing ratio of the deodorant substances, combining persimmon extract, glycine and chelating agent, a superabsorbent polymer composition with excellent deodorization ability is prepared. The composition comprises a base resin, a surface crosslinking layer, persimmon extract, glycine and a chelating agent, and the surface crosslinking layer is formed by heat treatment to enhance deodorization performance.
It is achieved that the deodorization ability is significantly improved without damaging the absorption performance and water retention ability of the superabsorbent polymer, and effectively removes odors caused by bacterial growth in the liquid.
Smart Images

Figure BDA0005236551390000331 
Figure BDA0005236551390000341 
Figure BDA0005236551390000351
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0182257 filed on December 22, 2022, and Korean Patent Application No. 10-2023-0164000 filed on December 23, 2023, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety. Technical Field
[0003] The present invention relates to a super absorbent polymer composition and a preparation method thereof. The present invention relates to a super absorbent polymer composition with deodorizing performance and a preparation method thereof. Background Art
[0004] Super absorbent polymer (SAP) is a synthetic polymer material that can absorb 500 to 1000 times its own weight in water. Various manufacturers have named it with different names, such as SAM (super absorbent material) and AGM (absorbent gel material). Such super absorbent polymers began to be practically used in sanitary products, and now they are widely used in water-retaining soil products for gardening, water-stopping materials for civil engineering and construction, sheets for seedling cultivation, preservatives for food circulation fields, or materials for plasters, etc.
[0005] These superabsorbent polymers have been widely used in the field of sanitary materials such as diapers or sanitary napkins. In such sanitary materials, superabsorbent polymers are generally contained in a state dispersed in pulp. However, in recent years, efforts have been made to provide sanitary materials such as diapers with thinner thickness. As part of such efforts, the development of so-called pulp-free diapers and the like in which the pulp content is reduced or no pulp is used at all is being actively carried out.
[0006] In the case of the above-mentioned sanitary material in which the pulp content is reduced or no pulp is used, the superabsorbent polymer is contained in a relatively high ratio, so that the superabsorbent polymer particles are inevitably contained in the sanitary material in a multi-layer form. In order to make the entire superabsorbent polymer particles contained in the multi-layer form more effectively absorb liquid such as urine, the superabsorbent polymer is basically required to show excellent absorption performance and high absorption rate. In addition, the absorbed liquid cannot flow out even under external pressure, and after absorbing the liquid, permeability is required to maintain its original shape even in a swollen state.
[0007] Therefore, many studies are being conducted to improve the basic absorbency and water-retaining capacity of superabsorbent polymers, such as surface cross-linking and the like.
[0008] However, superabsorbent polymers may be used for sanitary materials, and in this case, there may be a problem of reduced usability due to the odor of the absorbed liquid (such as human and pet excrement). In particular, it is necessary to suppress the odor contained in the liquid absorbed from the beginning and the odor caused by bacterial growth during the use of sanitary products containing superabsorbent polymers.
[0009] Therefore, deodorizing substances have been mixed with super absorbent polymers. However, there are problems in that absorbency is reduced by mixing an excessive amount of deodorizing substances in order to effectively suppress odor, or deodorizing ability to a desired degree cannot be achieved due to the focus on antibacterial properties.
[0010] Therefore, not only the basic properties (absorbency and water retention capacity) of super absorbent polymers are increasingly required, but also the odor suppression thereof is increasingly required. Therefore, it is necessary to provide a super absorbent polymer having excellent deodorizing ability. Summary of the invention
[0011] Technical issues
[0012] The present invention provides a super absorbent polymer composition with deodorizing performance and a preparation method thereof.
[0013] More particularly, the present invention relates to a super absorbent polymer composition having excellent deodorizing ability while minimizing deterioration of physical properties of the super absorbent polymer by controlling the combination and mixing ratio of deodorizing substances and a method for preparing the same.
[0014] Technical Solution
[0015] In order to solve the above problems, a superabsorbent polymer composition is provided, which comprises: a superabsorbent polymer comprising a base resin and a surface crosslinked layer, wherein the base resin contains a crosslinked polymer crosslinked and polymerized by an acrylic monomer having an acidic group that is at least partially neutralized and an internal crosslinking agent, and the surface crosslinked layer is formed by further crosslinking the crosslinked polymer using a surface crosslinking agent on the surface of the base resin; a persimmon extract; glycine; and a chelating agent.
[0016] In addition, a method for preparing a superabsorbent polymer composition is provided, comprising the following steps:
[0017] Forming a hydrogel polymer by cross-linking and polymerizing an acrylic monomer having at least partially neutralized acidic groups in the presence of an internal cross-linking agent and a polymerization initiator (step 1);
[0018] preparing a base resin containing a cross-linked polymer obtained by drying and pulverizing a hydrogel polymer (step 2);
[0019] preparing a mixture by mixing a surface cross-linking solution with a base resin (step 3); and
[0020] preparing a super absorbent polymer having a surface cross-linked layer formed on the surface of the base resin by heat-treating the mixture (step 4);
[0021] wherein the mixture containing the persimmon extract and glycine is mixed with the surface cross-linking solution of step 3, or is mixed with the super absorbent polymer having a surface cross-linking layer formed thereon in step 4, and
[0022] The chelating agent is mixed with the hydrogel polymer of step 1, mixed with the surface cross-linking solution of step 3, or mixed with the superabsorbent polymer having a surface cross-linking layer formed thereon of step 4.
[0023] Beneficial Effects
[0024] In the present invention, a super absorbent polymer composition having excellent deodorizing ability by applying a mixture containing a persimmon extract and glycine at an optimal ratio and a chelating agent to a super absorbent polymer and a method for preparing the same are provided. DETAILED DESCRIPTION
[0025] The terms used herein are only used to describe specific embodiments and are not intended to limit the present invention. Unless the context clearly indicates otherwise, the singular form is intended to also include the plural form. It will be further understood that when used in this specification, the terms "comprising", "having" or "having" specify the presence of the features, steps, components or combinations thereof, but do not exclude the presence or addition of one or more other features, steps, components or combinations thereof.
[0026] Since the present invention can be modified in various ways and has various forms, its specific embodiments are shown by way of example and will be described in detail. However, it is not intended to limit the present invention to the specific forms disclosed, and it should be understood that the present invention includes all modifications, equivalents and substitutions within the concept and technical scope of the present invention.
[0027] Since the present invention can be modified in various ways and has various forms, its specific embodiments are shown by way of example and will be described in detail. However, it is not intended to limit the present invention to the specific forms disclosed, and it should be understood that the present invention includes all modifications, equivalents and substitutions within the concept and technical scope of the present invention.
[0028] Hereinafter, a super absorbent polymer composition and a method for preparing the same will be described in more detail according to specific embodiments of the present invention.
[0029] The terms used herein are intended to refer to specific embodiments only and are not intended to limit the present invention. In addition, as used herein, the singular form also includes the plural form, unless the words clearly indicate otherwise.
[0030] For reference, depending on the context, the term "superabsorbent polymer" is used to cover superabsorbent polymers themselves as well as polymers that have been further processed (eg, surface crosslinking, fine particle reorganization, drying, pulverization, classification, etc.) into a state suitable for commercialization.
[0031] In addition, the "base resin" or "base resin powder" in the present invention is produced by drying and pulverizing a polymer in which an acrylic monomer is polymerized into particles or powder, and refers to a polymer that has not been subjected to surface modification or surface crosslinking described later.
[0032] (Superabsorbent polymer composition)
[0033] According to one embodiment of the present invention, a superabsorbent polymer composition is provided.
[0034] The superabsorbent polymer composition comprises: a superabsorbent polymer comprising a base resin and a cross-linked polymer cross-linked and polymerized by an acrylic monomer having at least partially neutralized acidic groups and an internal cross-linking agent, and a surface cross-linked layer formed by further cross-linking the cross-linked polymer using a surface cross-linking agent on the surface of the base resin; a persimmon extract; glycine; and a chelating agent.
[0035] The acrylic monomer may be any monomer commonly used in preparing superabsorbent polymers. Specifically, the acrylic monomer may be a compound represented by the following Chemical Formula 1:
[0036] [Chemical formula 1]
[0037] R 1 -COOM 1
[0038] In Chemical Formula 1,
[0039] R 1 is a C2 to C5 alkyl group having an unsaturated bond, and
[0040] M 1 It is a hydrogen atom, a monovalent or divalent metal, an ammonium group or an organic amine salt.
[0041] Preferably, the acrylic monomer may include at least one selected from the group consisting of acrylic acid, methacrylic acid, and monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts thereof.
[0042] The acrylic monomers may be those having at least partially neutralized acidic groups. Preferably, acrylic monomers partially neutralized with an alkali metal substance such as sodium hydroxide, potassium hydroxide, ammonium hydroxide, etc. may be used.
[0043] Here, the degree of neutralization of the monomer can be 40mol% to 95mol%, 40mol% to 80mol% or 45mol% to 75mol%. The range of the degree of neutralization can be adjusted according to the final properties. Too high a degree of neutralization causes precipitation of the neutralized monomer, so polymerization may not occur easily. On the contrary, too low a degree of neutralization not only deteriorates the absorbency of the polymer, but also imparts properties to the polymer that are difficult to handle, such as the properties of elastic rubber.
[0044] At the same time, it is carried out in the presence of a crosslinking agent ("internal crosslinking agent") to improve the physical properties of the polymer by polymerization of acrylic monomers. The crosslinking agent is used for internal crosslinking of the hydrogel polymer and can be used separately from the "surface crosslinking agent" described later.
[0045] As the internal cross-linking agent, any compound may be used as long as it allows introduction of a cross-linking bond during polymerization of the acrylic monomer. As a non-limiting example, the internal crosslinking agent may be a multifunctional crosslinking agent such as N,N′-methylenebisacrylamide, trimethylolpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butanediol di(meth)acrylate, butanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerol tri(meth)acrylate, pentaerythritol tetraacrylate, triarylamine, allyl (meth)acrylate, ethylene glycol diglycidyl ether, propylene glycol, glycerol or ethylene carbonate, and these may be used alone or in combination of two or more.
[0046] The internal crosslinking agent may be added at a concentration of 0.001 wt % to 1 wt %, 0.01 wt % to 0.8 wt %, or 0.1 wt % to 0.7 wt % based on the monomer composition. In other words, when the concentration of the internal crosslinking agent is too low, the absorption rate of the polymer may decrease and the gel strength may weaken, which is not preferred. Conversely, when the concentration of the internal crosslinking agent is too high, the absorbency of the polymer decreases, making it undesirable as an absorbent.
[0047] In addition, the base resin may further include additives such as a thickener, a plasticizer, a storage stabilizer, and an antioxidant, if necessary.
[0048] The surface crosslinked layer is formed by further crosslinking the crosslinked polymer using a surface crosslinking agent. As the surface crosslinking agent, any surface crosslinking agent capable of reacting with a functional group of a polymer commonly used in the preparation of a superabsorbent polymer may be used without any particular limitation.
[0049] Preferably, in order to improve the properties of the resulting superabsorbent polymer, the surface crosslinking agent may be at least one selected from the group consisting of: polyol compounds; epoxy compounds; polyamine compounds; halogenated epoxy compounds; condensation products of halogenated epoxy compounds; oxazoline compounds; mono-, di- or poly-oxazolidinone compounds; cyclic urea compounds; polyvalent metal salts; and alkylene carbonate compounds.
[0050] Specifically, as the polyol compound, at least one selected from the group consisting of mono-, di-, tri-, tetra- or polyethylene glycol, monopropylene glycol, 1,3-propylene glycol, dipropylene glycol, 2,3,4-trimethyl-1,3-pentanediol, polypropylene glycol, glycerol, polyglycerol, 2-butene-1,4-diol, 1,4-butanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol and 1,2-cyclohexanedimethanol can be used.
[0051] In addition, as the epoxy compound, ethylene glycol diglycidyl ether, glycidol, etc. can be used. As the polyamine compound, at least one selected from the group consisting of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneimine and polyamidepolyamine can be used.
[0052] In addition, as the halogenated epoxy compound, epichlorohydrin, epibromohydrin and α-methylepichlorohydrin can be used. Meanwhile, as the mono-, di- or poly-oxazolidinone compound, 2-oxazolidinone can be used.
[0053] In addition, as alkylene carbonate compounds, ethylene carbonate etc. can be used. These can be used alone or in combination with each other. At the same time, in order to improve the efficiency of the surface crosslinking process, one or more types of polyol-based compounds with 2 to 10 carbon atoms can be used in these surface crosslinking agents.
[0054] The content of the added surface crosslinking agent can be appropriately selected according to the type of the surface crosslinking agent or the reaction conditions, but it is generally about 0.001 to about 5 parts by weight, preferably about 0.01 to about 3 parts by weight, and more preferably about 0.05 to about 2 parts by weight, based on 100 parts by weight of the polymer.
[0055] When the content of the surface crosslinking agent is too small, the surface crosslinking reaction is difficult to occur. When it exceeds 5 parts by weight based on 100 parts by weight of the polymer, the absorption capacity and physical properties may be deteriorated due to excessive surface crosslinking reaction.
[0056] At the same time, the surface crosslinking agent can also include inorganic materials. As inorganic materials, at least one inorganic material selected from the group consisting of silicon dioxide, clay, aluminum oxide, silicon dioxide-alumina composite, titanium dioxide, zinc oxide and aluminum sulfate can be used. The inorganic material can be used in powdered form or in liquid form, and particularly, aluminum oxide powder, silicon dioxide-alumina powder, titanium dioxide powder or nano silicon dioxide solution can be used. In addition, based on 100 weight portions of the base resin, the amount of the inorganic material can be about 0.001 to about 1 weight portion.
[0057] The superabsorbent polymer composition of one embodiment of the present invention may contain persimmon extract and glycine as deodorizing substances. When persimmon extract and glycine are applied to sanitary products, they have the effect of removing the odor inherent in the liquid absorbed by the sanitary products and removing additional odor that may occur due to bacterial growth during use.
[0058] The persimmon extract may be a substance extracted from persimmon leaves, persimmon trunks / stems, persimmon fruits and persimmon roots. In addition, in the present invention, "extract" refers to the result of extraction using a suitable extraction solvent, and includes all preparations that can be formed using the extract, such as an extract obtained by extraction, a diluted or concentrated extract, a dry product obtained by drying the extract, a purified product or a portion thereof or a mixture thereof. However, the content, mixing amount, mixing ratio, etc. in the present invention are based on the solid content of the persimmon extract.
[0059] Glycine can capture odorous substances by chemically reacting with the odorous substances. Odorous substances generally have a small molecular weight, and when they react with glycine, they become substances with reduced or no odor. Therefore, glycine can effectively remove odors. In particular, glycine effectively reduces the odors of aldehyde and ketone compounds.
[0060] The content of glycine may be 100 to 200 parts by weight relative to 100 parts by weight of the persimmon extract calculated on a solid content basis. Preferably, the content of glycine may be 100 parts by weight or more, 120 parts by weight or more, 140 parts by weight or more, or 150 parts by weight or more and 200 parts by weight or less, 180 parts by weight or less, or 160 parts by weight or less relative to 100 parts by weight of the persimmon extract calculated on a solid content basis.
[0061] The content of the persimmon extract may be 0.005 to 0.050 parts by weight relative to 100 parts by weight of the base resin in terms of solid content. Preferably, the content of the persimmon extract in terms of solid content may be 0.005 parts by weight or more, 0.010 parts by weight or more, 0.015 parts by weight or more, 0.020 parts by weight or more, or 0.025 parts by weight or more to 0.050 parts by weight or less, 0.045 parts by weight or less, 0.040 parts by weight or less, 0.035 parts by weight or less, or 0.030 parts by weight or less relative to 100 parts by weight of the base resin.
[0062] In addition, the content of glycine may be 0.005 to 0.050 parts by weight relative to 100 parts by weight of the base resin. Specifically, the content of glycine may be 0.005 parts by weight or more, 0.010 parts by weight or more, 0.015 parts by weight or more, 0.020 parts by weight or more, 0.025 parts by weight or more, 0.030 parts by weight or more, or 0.035 parts by weight or more and 0.050 parts by weight or less, 0.045 parts by weight or less, or 0.040 parts by weight or less relative to 100 parts by weight of the base resin.
[0063] In order to maintain the unique absorption properties of the super absorbent polymer, maintain the white color of the absorbent from the viewpoint of aesthetics, and exhibit the deodorizing ability required by the present invention, it is preferred that the content of the persimmon extract or glycine as the deodorizing substance is within the above range.
[0064] When the solid content of the persimmon extract is greater than 0.050 parts by weight, physical properties such as absorbency may be reduced and the color of the absorbent may change from white to yellow. When it is less than 0.005 parts by weight, the deodorizing ability required by the present invention may not be achieved.
[0065] The superabsorbent polymer composition of one embodiment of the present invention may contain a chelating agent. In the case of sanitary products containing the superabsorbent polymer composition, when bacteria originating from the skin and absorbed liquid meet, additional odor may be generated due to the proliferation of bacteria, and the chelating agent can inhibit the growth of these bacteria.
[0066] The chelating agent may include an aminoacetic acid chelating agent. Specifically, the aminoacetic acid chelating agent may include at least one selected from the group consisting of ethylenediaminetetraacetic acid (EDTA), L-glutamic acid diacetic acid (GLDA), methylglycine diacetic acid (MGDA), hydroxyethylethylenediaminetriacetic acid (HEDTA), ethanol diglycine (EDG), diethylenetriaminepentaacetic acid (DTPA) and salts thereof. More specifically, the chelating agent may be ethylenediaminetetraacetic acid (EDTA) or L-glutamic acid diacetic acid (GLDA).
[0067] The content of the chelating agent may be 0.1 to 2.0 parts by weight relative to 100 parts by weight of the base resin. Specifically, the content of the chelating agent may be 0.1 parts by weight or more, 0.3 parts by weight or more, 0.5 parts by weight or more, 0.7 parts by weight or more, or 1.0 parts by weight or more to 2.0 parts by weight or less, 1.5 parts by weight or less, or 1.3 parts by weight or less relative to 100 parts by weight of the base resin.
[0068] In order to achieve the antibacterial activity required by the present invention while maintaining the unique absorption properties of the superabsorbent polymer, and inhibiting bacterial growth through antibacterial activity to exhibit deodorizing ability, it is preferred that the content of the chelating agent is within the above range.
[0069] When the content of the chelating agent is less than or equal to 0.1 parts by weight, it is difficult to achieve sufficient antimicrobial activity to inhibit bacteria, and when the content of the chelating agent is greater than or equal to 2.0 parts by weight, the physical properties of the superabsorbent polymer itself may deteriorate, such as reduced absorbency.
[0070] The superabsorbent polymer composition may further include one or more additives selected from the group consisting of organic acids, iodine compounds, glycerin, and zinc chloride.
[0071] The organic acid may be at least one selected from the group consisting of citric acid, acetic acid, formic acid, fumaric acid, lactic acid, and propionic acid. Specifically, the organic acid may be citric acid. The organic acid may exhibit a deodorizing effect in the superabsorbent polymer, such as persimmon extract or glycine. In addition, the organic acid has the effect of neutralizing ammonia dissolved in urine.
[0072] The iodine compound may be a metal iodide salt. The metal iodide salt may be added during the manufacturing process in the form of a solution in which one or more selected from the group consisting of CuI, NaI, KI and I2 are dissolved in water or in the form of a powder obtained by drying an aqueous solution. The metal iodide salt may also be added to a superabsorbent polymer to impart deodorizing properties, such as persimmon extract or glycine. The metal iodide salt removes unpleasant odors by oxidizing odorous substances and acts on most odorous substances, thereby being generally effective.
[0073] The persimmon extract, glycine and chelating agent may be contained independently in the base resin or in the surface crosslinked layer. Specifically, the persimmon extract or glycine may be contained in the surface crosslinked layer, and the chelating agent may be contained in the base resin or in the surface crosslinked layer.
[0074] The persimmon extract, glycine, chelating agent, organic acid or iodine compound may be mixed with the super absorbent polymer in the form of an aqueous solution using water as a solvent, and may exist in a state of being physically bound to the super absorbent polymer. Alternatively, it may be mixed with the super absorbent polymer in a powder form, and may exist in a state of being incorporated into the super absorbent polymer in a powder form.
[0075] (Method for preparing superabsorbent polymer composition)
[0076] According to one embodiment of the present invention, a method for preparing a superabsorbent polymer composition is provided.
[0077] The preparation method of the superabsorbent polymer composition comprises the following steps:
[0078] Forming a hydrogel polymer by crosslinking polymerization of an acrylic monomer having an at least partially neutralized acidic group in the presence of an internal crosslinking agent and a polymerization initiator (step 1); preparing a base resin containing a crosslinked polymer obtained by drying and pulverizing the hydrogel polymer (step 2); preparing a mixture by mixing a surface crosslinking solution with the base resin (step 3); and preparing a superabsorbent polymer having a surface crosslinked layer formed on the surface of the base resin by heat-treating the mixture (step 4);
[0079] wherein the mixture containing the persimmon extract and glycine is mixed with the surface cross-linking solution of step 3, or is mixed with the super absorbent polymer having a surface cross-linking layer formed thereon in step 4, and
[0080] The chelating agent is mixed with the hydrogel polymer of step 1, mixed with the surface cross-linking solution of step 3, or mixed with the superabsorbent polymer having a surface cross-linking layer formed thereon of step 4.
[0081] The method for preparing the super absorbent polymer includes the steps of polymerizing an acrylic monomer to prepare a hydrogel polymer and pulverizing the hydrogel polymer. In addition, in order to improve various physical properties of the super absorbent polymer, a method of cross-linking the surface of the prepared super absorbent polymer is used.
[0082] The present invention attempts to provide a superabsorbent polymer composition having deodorizing properties by mixing a surface-crosslinked superabsorbent polymer with a persimmon extract, glycine, and a chelating agent.
[0083] Hereinafter, the present invention will be described in detail for each step.
[0084] (Step 1)
[0085] Step 1 is a step of preparing a hydrogel polymer. Specifically, it is a step of forming a hydrogel polymer by cross-linking and polymerizing a monomer composition containing an acrylic monomer having an at least partially neutralized acidic group.
[0086] The acrylic monomer may be any monomer commonly used in preparing superabsorbent polymers. Specifically, the acrylic monomer may be a compound represented by the following Chemical Formula 1:
[0087] [Chemical formula 1]
[0088] R 1 -COOM 1
[0089] In Chemical Formula 1,
[0090] R 1 is a C2 to C5 alkyl group having an unsaturated bond, and
[0091] M 1 It is a hydrogen atom, a monovalent or divalent metal, an ammonium group or an organic amine salt.
[0092] Preferably, the acrylic monomer may include at least one selected from the group consisting of acrylic acid, methacrylic acid, and monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts thereof.
[0093] The acrylic monomers may be those having at least partially neutralized acidic groups. Preferably, acrylic monomers partially neutralized with an alkali metal substance such as sodium hydroxide, potassium hydroxide or ammonium hydroxide may be used.
[0094] Here, the degree of neutralization of the monomer may be 40-95 mol%, 40-80 mol%, or 45-75 mol%. The range of the degree of neutralization can be adjusted according to the final properties. Too high a degree of neutralization results in precipitation of the neutralized monomer, so that polymerization may not occur easily. On the contrary, too low a degree of neutralization not only deteriorates the absorbency of the polymer, but also imparts properties to the polymer that are difficult to handle, such as the properties of elastic rubber.
[0095] The monomer composition may contain a polymerization initiator commonly used in the preparation of superabsorbent polymers.
[0096] Depending on the polymerization method, the polymerization initiator may be a thermal polymerization initiator or a photopolymerization initiator. However, even in the case of a photopolymerization method, a certain amount of heat is generated by light irradiation such as ultraviolet irradiation. In addition, a certain amount of heat may be generated as the polymerization reaction proceeds (i.e., an exothermic reaction), and a thermal polymerization initiator may also be used.
[0097] For example, the photopolymerization initiator can be one or more selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyalkyl ketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine and α-amino ketone. Meanwhile, as a specific example of acyl phosphine, commercially available Lucirin TPO, i.e. 2,4,,6-trimethyl-benzoyl-trimethylphosphine oxide, can be used. More photopolymerization initiators are fully disclosed on page 115 of "UV Coatings: Basics, Recent Developments and New Application (Elsevier, 2007)" written by Reinhold Schwalm, and the present invention is not limited thereto.
[0098] In addition, one or more initiators selected from the group consisting of persulfate initiators, azo initiators, hydrogen peroxide and ascorbic acid can be used as thermal polymerization initiators. Specifically, sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8) and ammonium persulfate ((NH4)2S2O8) can be used as examples of persulfate initiators; and 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, 2-(carbamoyl azo)isobutyronitrile, 2,2-azobis[2-(2-imidazoline-2-yl)propane] dihydrochloride and 4,4-azobis-(4-cyanovaleric acid) can be used as examples of azo initiators. More various thermal polymerization initiators are fully disclosed in "Principle of Polymerization (Wiley, 1981)" by Odian, page 203, and the present invention is not limited thereto.
[0099] The polymerization initiator may be added at a concentration of 0.001 to 1% by weight or 0.005 to 0.1% by weight based on the monomer composition. In other words, when the concentration of the polymerization initiator is too low, the polymerization rate may be slowed down, and thus a large amount of residual monomers may be extracted from the final product, which is not preferred. On the contrary, when the concentration of the polymerization initiator is too high, the polymer chains forming the network may become shorter, and thus the physical properties of the polymer may be deteriorated, such as an increase in the content of water-soluble components and a decrease in pressure absorbency, which is not preferred.
[0100] Meanwhile, the polymerization of the monomer composition is carried out in the presence of a crosslinking agent ("internal crosslinking agent") to improve the physical properties of the polymer by polymerization of the acrylic monomer. The crosslinking agent is used for internal crosslinking of the hydrogel polymer and can be used separately from the "surface crosslinking agent" described later.
[0101] As the internal cross-linking agent, any compound may be used as long as it allows introduction of a cross-linking bond during polymerization of the acrylic monomer. As a non-limiting example, the internal crosslinking agent may be a multifunctional crosslinking agent such as N,N′-methylenebisacrylamide, trimethylolpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butanediol di(meth)acrylate, butanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerol tri(meth)acrylate, pentaerythritol tetraacrylate, triarylamine, allyl (meth)acrylate, ethylene glycol diglycidyl ether, propylene glycol, glycerol or ethylene carbonate, and these may be used alone or in combination of two or more.
[0102] The internal crosslinking agent may be added at a concentration of 0.001 to 1 wt%, 0.01 to 0.8 wt%, or 0.1 to 0.7 wt%, based on the monomer composition. In other words, when the concentration of the internal crosslinking agent is too low, the absorption rate of the polymer may decrease and the gel strength may weaken, which is not preferred. Conversely, when the concentration of the internal crosslinking agent is too high, the absorbency of the polymer decreases, making it undesirable as an absorbent.
[0103] In addition, the cross-linking polymerization of the monomer composition may be carried out in the presence of a foaming agent, depending on the need and degree of improvement of the absorption rate. Such a foaming agent may decompose during the cross-linking polymerization to generate a gas, thereby forming pores in the hydrogel polymer. Therefore, when such a foaming agent is additionally used, a more porous structure is formed in the superabsorbent polymer, thereby further improving the absorption rate of the superabsorbent polymer.
[0104] As a non-limiting example, the foaming agent may include at least one compound selected from the group consisting of sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, calcium bicarbonate, calcium carbonate, magnesium bicarbonate, magnesium carbonate, azodicarbonamide (ADCA), dinitropentamethylenetetramine (DPT), p,p'-oxybis(benzenesulfonylhydrazide) (OBSH), p-toluenesulfonylhydrazide (TSH), sucrose stearate, sucrose palmitate, and sucrose laurate.
[0105] The blowing agent may be present in the monomer composition in an amount of 1000 to 4000 ppmw. More specifically, it may be present in an amount of 1000 ppm or more, 1100 ppm or more, or 1200 ppmw or more and 4000 ppmw or less, 3500 ppmw or less, or 3000 ppmw or less.
[0106] In addition, if necessary, the monomer composition may further include a thickener, a plasticizer, an antiseptic stabilizer, an antioxidant, and the like.
[0107] In addition, such a monomer composition may be prepared in the form of a solution in which raw materials such as the above-mentioned acrylic monomer, polymerization initiator, internal crosslinking agent and foaming agent are dissolved in a solvent.
[0108] At this time, any solvent that can dissolve the raw materials can be used without restriction, for example, water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, N,N-dimethylacetamide or a mixture thereof can be used.
[0109] The process of forming the hydrogel polymer by polymerizing the monomer composition may be performed by a conventional polymerization method, and the method is not particularly limited.
[0110] As a non-limiting example, depending on the energy source of polymerization, polymerization methods are mainly divided into thermal polymerization and photopolymerization. In the case of thermal polymerization, it is usually carried out in a reactor (e.g., a kneader) equipped with a stirring spindle. In the case of photopolymerization, it can be carried out in a reactor equipped with a movable conveyor belt.
[0111] For example, the hydrogel polymer can be obtained by introducing the monomer composition into a reactor (e.g., a kneader) equipped with a stirring shaft, and then supplying hot air or heating the reactor to perform thermal polymerization. Depending on the shape of the stirring shaft provided in the reactor, the hydrogel polymer can be discharged to the reactor outlet in the form of particles of several centimeters to several millimeters. Specifically, the shape of the obtained hydrogel polymer can vary according to the concentration and injection rate of the monomer mixture to be injected, and a hydrogel polymer with a (weight average) particle size of 2 to 50 mm can usually be obtained.
[0112] As another example, when the monomer composition is photopolymerized in a reactor equipped with a movable conveyor, a hydrogel polymer in the form of a sheet can be obtained. At this time, the thickness of the sheet can be varied according to the concentration of the monomer composition to be injected and the injection rate. It is preferred that the thickness is adjusted to 0.5 to 10 cm to ensure productivity while uniformly polymerizing the entire sheet.
[0113] The hydrogel polymer formed in this manner may exhibit a water content of 40 to 80% by weight. At this time, the water content is the weight of the water in the total weight of the hydrogel polymer, which refers to the value obtained by subtracting the weight of the dry polymer from the weight of the hydrogel polymer. Specifically, the water content is defined as a value calculated by measuring the weight loss due to evaporation of water from the polymer during the process of increasing the polymer temperature by infrared heating for drying. At this time, the drying conditions are as follows: the temperature is raised to about 180°C and maintained at 180°C, and the total drying time is 20 minutes, including a heating step of 5 minutes.
[0114] The chelating agent may be mixed with the hydrogel polymer prepared in step 1 before drying, pulverizing and classifying in step 2. In step 1, the hydrogel polymer may be prepared in the form of a sheet and mixed by cutting the sheet while spraying the chelating agent.
[0115] The chelating agent may include an aminoacetic acid chelating agent. Specifically, the aminoacetic acid chelating agent may include at least one selected from the group consisting of ethylenediaminetetraacetic acid (EDTA), L-glutamic acid diacetic acid (GLDA), methylglycine diacetic acid (MGDA), hydroxyethylethylenediaminetriacetic acid (HEDTA), ethanol diglycine (EDG), diethylenetriaminepentaacetic acid (DTPA) and salts thereof. More specifically, the chelating agent may be ethylenediaminetetraacetic acid (EDTA) or L-glutamic acid diacetic acid (GLDA).
[0116] The content of the chelating agent may be 0.1 to 2.0 parts by weight relative to 100 parts by weight of the base resin. Specifically, the content of the chelating agent may be 0.1 parts by weight or more, 0.3 parts by weight or more, 0.5 parts by weight or more, 0.7 parts by weight or more, or 1.0 parts by weight or more to 2.0 parts by weight or less, 1.5 parts by weight or less, or 1.3 parts by weight or less relative to 100 parts by weight of the base resin.
[0117] In order to exhibit deodorizing ability by inhibiting bacterial growth as required by the present invention while maintaining unique absorption properties such as absorption of the superabsorbent polymer, it is preferred that the content of the chelating agent is within the above range.
[0118] The chelating agent can be mixed into the base resin in the form of an aqueous solution or a powder.
[0119] (Step 2)
[0120] Step 2 of the present invention is a step of drying, pulverizing and classifying the hydrogel polymer prepared in step 1 to form a base resin powder.
[0121] Specifically, the present invention may further include a step of coarsely pulverizing the hydrogel polymer before drying to increase the absorption rate of the superabsorbent polymer. Coarse pulverization not only improves the drying efficiency of the hydrogel polymer, but also affects the morphology of the superabsorbent polymer, which may affect various physical properties of the superabsorbent polymer, including the absorption rate. Hereinafter, in order to distinguish it from the pulverization after drying, the term "coarse pulverization" is used for the pulverization before drying.
[0122] At this time, the structure of the pulverizer used in the pulverizing step is not limited. Specifically, at least one pulverizer selected from the group consisting of a vertical pulverizer, a turbine cutter, a turbine grinder, a rotary shredder, a shredder, a disc grinder, a shred crusher, a crusher, a cutter, and a disc cutter can be used, but the present invention is not limited thereto.
[0123] Herein, the hydrogel polymer may be coarsely pulverized so that the particle size is about 2 mm to about 10 mm. Due to the high water content of the hydrogel polymer, pulverization to a particle size of less than 2 mm is not technically easy, and agglomeration between pulverized particles may occur. On the other hand, when pulverized to a particle size greater than 10 mm, the increase in the efficiency of the subsequent drying step may not be significant.
[0124] Drying can be performed at a temperature of 120°C to 250°C, 140°C to 200°C, or 150°C to 190°C. In this case, the drying temperature can be defined as the temperature of the heating medium used for drying or the temperature inside the drying reactor of the heating medium and the polymer during the drying process. When the drying time is extended due to the low drying temperature, the process efficiency is reduced. To prevent this, the drying temperature is preferably 120°C or more. In addition, when the drying temperature is too high, the surface of the hydrogel polymer is over-dried, which may increase the generation of fine particles in the subsequent pulverization step, thereby reducing the physical properties of the final polymer. To prevent this, the drying temperature is preferably 250°C or less.
[0125] Herein, the drying time may be about 20 minutes to about 90 minutes in consideration of process efficiency and physical properties of the polymer, but is not limited thereto.
[0126] Drying can be carried out using common media, such as by hot air supply, infrared radiation, microwave radiation, UV ray radiation and the like.
[0127] In addition, it is preferred to dry the polymer so that the water content of the dried polymer is 0.1 to 10% by weight. In other words, when the water content of the dried polymer is less than 0.1% by weight, excessive drying may increase the manufacturing cost and cause degradation of the cross-linked polymer, which is undesirable. In addition, when the water content of the dried polymer exceeds 10% by weight, defects may occur in subsequent processes, which is undesirable.
[0128] Subsequently, the dried hydrogel polymer may be pulverized. This is a step to optimize the surface area of the base resin powder and the superabsorbent polymer. The pulverization may be performed so that the particle size of the pulverized polymer is 150 μm to 850 μm.
[0129] As the pulverizer, a pin mill, a hammer mill, a screw mill, a roller mill, a disk mill, a jog mill, or the like can be used.
[0130] In order to control the physical properties of the super absorbent polymer to be prepared as a final product, a step of selectively classifying particles having a particle size of 150 μm to 850 μm from the polymer particles obtained through the pulverization step is performed.
[0131] After the classification step, a base resin powder may be obtained. The base resin powder may have a particle size of 150 μm to 850 μm, and may contain 2 wt % or less or 1 wt % or less of fine powder having a particle size of less than 150 μm.
[0132] In addition, after the base resin powder is obtained by drying and pulverizing, a step of mixing zirconium phosphate may be further included. In this case, the zirconium phosphate may be dry mixed. In other words, the zirconium phosphate may be physically mixed in the base resin as a solid content in a dry manner before surface cross-linking. Zirconium phosphate is a substance that can physically adsorb odorous substances. Therefore, by further mixing zirconium phosphate with the base resin powder, an additional deodorizing effect may be achieved.
[0133] At this time, the content of zirconium phosphate may be 5.0 parts by weight or less relative to 100 parts by weight of the base resin. Zirconium phosphate is additionally used to improve the deodorizing ability and may not be included. When zirconium phosphate is included, its content may be 0.5 parts by weight or more, 0.8 parts by weight or more, 1.0 parts by weight or more, 1.3 parts by weight or more, 1.5 parts by weight or more, or 1.8 parts by weight or more, and 5.0 parts by weight or less, 4.0 parts by weight or less, 3.0 parts by weight or less, or 2.0 parts by weight or less. When too little zirconium phosphate is mixed, there may be a problem that the deodorizing effect of zirconium phosphate is not obvious, and when too much zirconium phosphate is included, there may be a problem that the absorbency under pressure is reduced due to poor surface crosslinking.
[0134] (Step 3)
[0135] Step 3 of the present invention is a step of mixing the surface cross-linking solution with the base resin powder prepared in step 2.
[0136] The surface crosslinking solution used in step 3 contains a surface crosslinking agent. The surface crosslinking agent is not particularly limited as long as it is a compound that can react with the functional groups of the polymer. It is generally used for surface crosslinking of superabsorbent polymers.
[0137] Preferably, in order to improve the properties of the resulting superabsorbent polymer, the surface crosslinking agent may be at least one selected from the group consisting of: polyol compounds; epoxy compounds; polyamine compounds; halogenated epoxy compounds; condensation products of halogenated epoxy compounds; oxazoline compounds; mono-, di- or poly-oxazolidinone compounds; cyclic urea compounds; polyvalent metal salts; and alkylene carbonate compounds.
[0138] Specifically, as the polyol compound, at least one selected from the group consisting of mono-, di-, tri-, tetra- or polyethylene glycol, monopropylene glycol, 1,3-propylene glycol, dipropylene glycol, 2,3,4-trimethyl-1,3-pentanediol, polypropylene glycol, glycerol, polyglycerol, 2-butene-1,4-diol, 1,4-butanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol and 1,2-cyclohexanedimethanol can be used.
[0139] In addition, as the epoxy compound, ethylene glycol diglycidyl ether, glycidol, etc. can be used. As the polyamine compound, at least one selected from the group consisting of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneimine and polyamidepolyamine can be used.
[0140] In addition, as the halogenated epoxy compound, epichlorohydrin, epibromohydrin and α-methylepichlorohydrin can be used. Meanwhile, as the mono-, di- or poly-oxazolidinone compound, 2-oxazolidinone can be used.
[0141] In addition, as alkylene carbonate compounds, ethylene carbonate can be used. These can be used alone or in combination with each other. Meanwhile, in order to improve the efficiency of the surface crosslinking process, one or more types of polyol-based compounds with 2 to 10 carbon atoms can be used in these surface crosslinking agents.
[0142] The content of the added surface crosslinking agent can be appropriately selected according to the type of the surface crosslinking agent or the reaction conditions, but it is generally about 0.001 to about 5 parts by weight, preferably about 0.01 to about 3 parts by weight, and more preferably about 0.05 to about 2 parts by weight, based on 100 parts by weight of the polymer.
[0143] When the content of the surface crosslinking agent is too small, the surface crosslinking reaction is difficult to occur. When it exceeds 5 parts by weight based on 100 parts by weight of the polymer, the absorption capacity and physical properties may be deteriorated due to excessive surface crosslinking reaction.
[0144] Meanwhile, the step of forming the surface crosslinking layer can be carried out by additionally comprising inorganic material in the surface crosslinking solution. As inorganic material, at least one inorganic material selected from the group consisting of silicon dioxide, clay, aluminum oxide, silicon dioxide-alumina composite, titanium dioxide, zinc oxide and aluminum sulfate can be used. Inorganic material can be used in powdered form or in liquid form, especially, aluminum oxide powder, silicon dioxide-alumina powder, titanium dioxide powder or nano silicon dioxide solution can be used. In addition, based on the base resin of 100 weight parts, the consumption of inorganic material can be about 0.001 to about 1 weight part.
[0145] In addition, a mixture containing persimmon extract and glycine may be mixed with the base resin together with the surface cross-linking solution. Persimmon extract and glycine may chemically bind to volatile odorous substances such as aldehydes, thereby imparting deodorizing ability to the super absorbent polymer.
[0146] The content of glycine may be 100 to 200 parts by weight relative to 100 parts by weight of the persimmon extract in terms of solid content. Preferably, the content of glycine may be 100 parts by weight or more, 120 parts by weight or more, 140 parts by weight or more, or 150 parts by weight or more and 200 parts by weight or less, 180 parts by weight or less, or 160 parts by weight or less relative to 100 parts by weight of the persimmon extract in terms of solid content.
[0147] The content of the persimmon extract in terms of solid content may be 0.005 to 0.050 parts by weight relative to 100 parts by weight of the base resin. Preferably, the content of the persimmon extract in terms of solid content may be 0.005 parts by weight or more, 0.010 parts by weight or more, 0.015 parts by weight or more, 0.020 parts by weight or more, or 0.025 parts by weight or more to 0.050 parts by weight or less, 0.045 parts by weight or less, 0.040 parts by weight or less, 0.035 parts by weight or less, or 0.030 parts by weight or less, relative to 100 parts by weight of the base resin.
[0148] In addition, the content of glycine may be 0.005 to 0.050 parts by weight relative to 100 parts by weight of the base resin. Specifically, the content of glycine may be 0.005 parts by weight or more, 0.010 parts by weight or more, 0.015 parts by weight or more, 0.020 parts by weight or more, 0.025 parts by weight or more, 0.030 parts by weight or more, or 0.035 parts by weight or more and 0.050 parts by weight or less, 0.045 parts by weight or less, or 0.040 parts by weight or less relative to 100 parts by weight of the base resin.
[0149] In order to express the deodorizing ability required by the present invention while maintaining the unique absorption properties of the super absorbent polymer, it is preferred that the content of the persimmon extract or glycine as the deodorizing substance is within the above range.
[0150] The deodorant material containing persimmon extract and glycine may be mixed in a base resin in the form of an aqueous solution or a powder.
[0151] In addition, the chelating agent can be mixed in the base resin together with the surface cross-linking solution. For details on the type, mixing amount and mixing form of the chelating agent, see step 1.
[0152] Meanwhile, the method of mixing the surface cross-linking solution with the base resin is not particularly limited and may be appropriately selected as long as it is a method capable of uniformly mixing the surface cross-linking solution with the base resin.
[0153] For example, the following methods may be used: a method of adding a surface crosslinking solution and a base resin in a reactor to mix; a method of spraying the surface crosslinking solution onto the base resin; or a method of mixing the base resin and the surface crosslinking solution and simultaneously continuously supplying them to a continuously operating mixer.
[0154] At this time, the surface cross-linking solution may be an aqueous solution, and the solid content in the solution may be 1 wt % or more, 3 wt % or more, 5 wt % or more, or 10 wt % or more, and 50 wt % or less, 30 wt % or less, or 20 wt % or less, so as to be uniformly dispersed in the base resin and prevent agglomeration of the base resin.
[0155] (Step 4)
[0156] Step 4 is a step of further improving the physical properties of the superabsorbent polymer by reacting the base resin with a surface crosslinking solution to form an interpenetrating polymer network on the surface of the crosslinked polymer contained in the base resin. Through this surface modification, a surface crosslinking layer is formed on the surface of the pulverized base resin particles.
[0157] The formation of the surface crosslinked layer can be performed by a conventional method of increasing the crosslinking density of the polymer particle surface, for example, by mixing a surface crosslinking solution containing a surface crosslinking agent with a pulverized polymer and then heat-treating it to perform a crosslinking reaction.
[0158] Step 4 may be performed at a temperature of about 80°C to about 250°C. More specifically, the surface crosslinking process may be performed at a temperature of about 100°C to about 220°C, about 110°C to about 200°C, or about 120°C to about 190°C for about 10 minutes to about 2 hours or about 20 minutes to about 60 minutes. When the crosslinking reaction temperature is lower than 160°C or the reaction time is too short, the surface crosslinking reaction may not properly occur and the permeability may be reduced. When it exceeds 200°C or the reaction time is too long, the water retention capacity may be reduced.
[0159] The heating means for the surface cross-linking reaction is not particularly limited. A thermal medium can be provided thereto or a heat source can be directly provided thereto. At this time, the available thermal medium can be a heated fluid, such as steam, hot air, hot oil, etc., but the present invention is not limited thereto. In addition, the temperature of the thermal medium provided thereto can be appropriately selected by considering the means of the thermal medium, the heating rate and the target temperature of the heating. Meanwhile, an electric heater or a gas heater can be directly provided as a heat source, but the present invention is not limited thereto.
[0160] In addition, the mixture containing the persimmon extract and glycine may be mixed with the super absorbent polymer having a surface cross-linked layer formed thereon. For details on the mixing amount and mixing form of the persimmon extract and glycine, see step 3.
[0161] In addition, a chelating agent may be mixed with the super absorbent polymer having a surface cross-linked layer formed thereon. For details on the kind, mixing amount and mixing form of the chelating agent, see step 1.
[0162] In addition, one or more additives selected from the group consisting of organic acids, iodine compounds, glycerin, and zinc chloride may be further mixed with the super absorbent polymer having the surface cross-linked layer formed thereon.
[0163] The organic acid may be at least one selected from the group consisting of citric acid, acetic acid, formic acid, fumaric acid, lactic acid, and propionic acid. Specifically, the organic acid may be citric acid. The organic acid may exhibit a deodorizing effect in the super absorbent polymer, such as persimmon extract or glycine.
[0164] The iodine compound may be an iodide metal salt. The iodide metal salt may be added during the manufacturing process in the form of a solution in which one or more selected from the group consisting of CuI, NaI, KI and I2 are dissolved in water or in the form of a powder obtained by drying an aqueous solution. The iodide metal salt may also be added to the superabsorbent polymer to impart deodorizing properties, like a deodorizing substance. The iodide metal salt removes unpleasant odors by oxidizing odorous substances and acts on most odorous substances, thereby being generally effective.
[0165] The organic acid or the iodine compound may be mixed in the form of an aqueous solution using water as a solvent or in the form of a powder.
[0166] When a deodorizing substance and a chelating agent are subsequently added as an aqueous solution to the super absorbent polymer having the surface cross-linked layer formed thereon, a drying step may be additionally performed.
[0167] Hereinafter, preferred embodiments are given to facilitate understanding of the present invention. However, the following embodiments are only for illustrative purposes and are not intended to limit the present invention.
[0168] Preparation Example 1-Mixture A
[0169] The persimmon extract and glycine were prepared as an aqueous solution. At this time, 5 parts by weight of the persimmon extract (in terms of solid content) and 5 parts by weight of glycine were mixed with respect to 100 parts by weight of the aqueous solution.
[0170] Preparation Example 2-Mixture B
[0171] The persimmon extract and glycine were prepared as an aqueous solution. At this time, 5 parts by weight of the persimmon extract (in terms of solid content) and 7 parts by weight of glycine were mixed with respect to 100 parts by weight of the aqueous solution.
[0172] Comparative Preparation Example 1 - Mixture C
[0173] The persimmon extract and methionine were prepared as an aqueous solution. At this time, 5 parts by weight of the persimmon extract (in terms of solid content) and 5 parts by weight of methionine were mixed with respect to 100 parts by weight of the aqueous solution.
[0174] Comparative Example 1
[0175] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0176] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying a polymer having a particle size of 150 μm to 850 μm using a sieve.
[0177] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0178] Comparative Example 2
[0179] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0180] The prepared hydrogel polymer was in the form of a sheet, and the sheet was cut into small pieces. An EDTA aqueous solution (EDTA concentration of 40%) was sprayed onto the cut hydrogel polymer and mixed by chopping (hole size: 16 mm). At this time, 0.5 parts by weight of EDTA was mixed relative to 100 parts by weight of the base resin.
[0181] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying a polymer having a particle size of 150 μm to 850 μm using a sieve.
[0182] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0183] Comparative Example 3
[0184] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0185] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0186] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S), and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0187] With respect to 100 parts by weight of the base resin, 0.3 parts by weight of the mixture A in an aqueous solution was mixed with the surface-treated superabsorbent polymer. Then, a drying step was performed at 80° C. for 25 minutes.
[0188] Comparative Example 4
[0189] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0190] The prepared hydrogel polymer was in the form of a sheet, and the sheet was cut into small pieces. An EDTA aqueous solution (EDTA concentration of 40%) was sprayed onto the cut hydrogel polymer and mixed by chopping (hole size: 16 mm). At this time, 0.5 parts by weight of EDTA was mixed relative to 100 parts by weight of the base resin.
[0191] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0192] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0193] 0.3 parts by weight of the mixture C in aqueous solution was mixed with the surface-treated superabsorbent polymer relative to 100 parts by weight of the base resin. Then, a drying step was performed at 80° C. for 25 minutes.
[0194] Comparative Example 5
[0195] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0196] The prepared hydrogel polymer was in the form of a sheet, and the sheet was cut into small pieces. An EDTA aqueous solution (EDTA concentration of 40%) was sprayed onto the cut hydrogel polymer and mixed by chopping (hole size: 16 mm). At this time, 0.5 parts by weight of EDTA was mixed relative to 100 parts by weight of the base resin.
[0197] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0198] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0199] The glycine aqueous solution was mixed with the surface-treated super absorbent polymer so that 0.015 parts by weight of glycine was added relative to 100 parts by weight of the base resin. Then, a drying step was performed at 80° C. for 25 minutes.
[0200] Comparative Example 6
[0201] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0202] The prepared hydrogel polymer is in the form of a sheet, and the sheet is cut into small pieces.
[0203] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0204] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0205] The aqueous solution of persimmon extract was mixed with the surface-treated super absorbent polymer so that the solid content of persimmon extract was 0.015 parts by weight relative to 100 parts by weight of the base resin. Then, a drying step was performed at 80° C. for 25 minutes.
[0206] Comparative Example 7
[0207] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0208] The prepared hydrogel polymer is in the form of a sheet, and the sheet is cut into small pieces.
[0209] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0210] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0211] The glycine aqueous solution was mixed with the surface-treated super absorbent polymer so that 0.015 parts by weight of glycine was added relative to 100 parts by weight of the base resin. Then, a drying step was performed at 80° C. for 25 minutes.
[0212] Example 1
[0213] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0214] The prepared hydrogel polymer was in the form of a sheet, and the sheet was cut into small pieces. An EDTA aqueous solution (EDTA concentration of 40%) was sprayed onto the cut hydrogel polymer and mixed by chopping (hole size: 16 mm). At this time, 0.5 parts by weight of EDTA was mixed relative to 100 parts by weight of the base resin.
[0215] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0216] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0217] 0.1 parts by weight of the mixture A in an aqueous solution was mixed with the surface-treated superabsorbent polymer relative to 100 parts by weight of the base resin. Then, a drying step was performed at 80° C. for 25 minutes.
[0218] Example 2
[0219] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0220] The prepared hydrogel polymer was in the form of a sheet, and the sheet was cut into small pieces. An EDTA aqueous solution (EDTA concentration of 40%) was sprayed onto the cut hydrogel polymer and mixed by chopping (hole size: 16 mm). At this time, 0.5 parts by weight of EDTA was mixed relative to 100 parts by weight of the base resin.
[0221] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0222] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0223] 0.3 parts by weight of the mixture A in an aqueous solution was mixed with the surface-treated super absorbent polymer relative to 100 parts by weight of the base resin. Then, a drying step was performed at 80° C. for 25 minutes.
[0224] Example 3
[0225] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0226] The prepared hydrogel polymer was in the form of a sheet, and the sheet was cut into small pieces. An EDTA aqueous solution (EDTA concentration of 40%) was sprayed onto the cut hydrogel polymer and mixed by chopping (hole size: 16 mm). At this time, 0.5 parts by weight of EDTA was mixed relative to 100 parts by weight of the base resin.
[0227] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0228] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0229] 0.5 parts by weight of the mixture A in an aqueous solution was mixed with the surface-treated super absorbent polymer relative to 100 parts by weight of the base resin. Then, a drying step was performed at 80° C. for 25 minutes.
[0230] Example 4
[0231] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0232] The prepared hydrogel polymer was in the form of a sheet, and the sheet was cut into small pieces. An EDTA aqueous solution (EDTA concentration of 40%) was sprayed onto the cut hydrogel polymer and mixed by chopping (hole size: 16 mm). At this time, 0.5 parts by weight of EDTA was mixed relative to 100 parts by weight of the base resin.
[0233] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0234] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0235] 0.1 parts by weight of the mixture B in an aqueous solution was mixed with the surface-treated super absorbent polymer relative to 100 parts by weight of the base resin. Then, a drying step was performed at 80° C. for 25 minutes.
[0236] Example 5
[0237] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0238] The prepared hydrogel polymer was in the form of a sheet, and the sheet was cut into small pieces. An EDTA aqueous solution (EDTA concentration of 40%) was sprayed onto the cut hydrogel polymer and mixed by chopping (hole size: 16 mm). At this time, 0.5 parts by weight of EDTA was mixed relative to 100 parts by weight of the base resin.
[0239] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0240] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0241] 0.3 parts by weight of the mixture B in an aqueous solution was mixed with the surface-treated super absorbent polymer relative to 100 parts by weight of the base resin. Then, a drying step was performed at 80° C. for 25 minutes.
[0242] Example 6
[0243] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0244] The prepared hydrogel polymer was in the form of a sheet, and the sheet was cut into small pieces. An EDTA aqueous solution (EDTA concentration of 40%) was sprayed onto the cut hydrogel polymer and mixed by chopping (hole size: 16 mm). At this time, 0.5 parts by weight of EDTA was mixed relative to 100 parts by weight of the base resin.
[0245] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0246] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0247] 0.5 parts by weight of the mixture B in an aqueous solution was mixed with the surface-treated super absorbent polymer relative to 100 parts by weight of the base resin. Then, a drying step was performed at 80° C. for 25 minutes.
[0248] Example 7
[0249] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0250] The prepared hydrogel polymer was in the form of a sheet, and the sheet was cut into small pieces. An EDTA aqueous solution (EDTA concentration of 40%) was sprayed onto the cut hydrogel polymer and mixed by chopping (hole size: 16 mm). At this time, 0.5 parts by weight of EDTA was mixed relative to 100 parts by weight of the base resin.
[0251] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0252] Afterwards, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)). Further, 100 parts by weight of the above-prepared base resin was mixed with 0.3 parts by weight of mixture A in an aqueous solution. Then, a surface crosslinking reaction was performed at 140°C for 30 minutes. After the surface treatment was completed, a superabsorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0253] Example 8
[0254] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0255] The prepared hydrogel polymer was in the form of a sheet, and the sheet was cut into small pieces. An EDTA aqueous solution (EDTA concentration of 40%) was sprayed onto the cut hydrogel polymer and mixed by chopping (hole size: 16 mm). At this time, 1.0 part by weight of EDTA was mixed relative to 100 parts by weight of the base resin.
[0256] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0257] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0258] 0.3 parts by weight of the mixture A in an aqueous solution was mixed with the surface-treated super absorbent polymer relative to 100 parts by weight of the base resin. Then, a drying step was performed at 80° C. for 25 minutes.
[0259] Example 9
[0260] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0261] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0262] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0263] An EDTA aqueous solution (EDTA concentration of 40%) and mixture A were mixed with the surface-treated superabsorbent polymer. At this time, 0.5 parts by weight of EDTA was mixed with respect to 100 parts by weight of the base resin. In addition, 0.3 parts by weight of mixture A in an aqueous solution was mixed with respect to 100 parts by weight of the base resin. Then, a drying step was performed at 80° C. for 25 minutes.
[0264] Example 10
[0265] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0266] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0267] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0268] An EDTA aqueous solution (EDTA concentration of 40%) and mixture A were mixed with the surface-treated superabsorbent polymer. At this time, 1.0 part by weight of EDTA was mixed with respect to 100 parts by weight of the base resin. In addition, 0.3 parts by weight of mixture A in an aqueous solution was mixed with respect to 100 parts by weight of the base resin. Then, a drying step was performed at 80° C. for 25 minutes.
[0269] Embodiment 11
[0270] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0271] The prepared hydrogel polymer was in the form of a sheet, and the sheet was cut into small pieces. A GLDA aqueous solution (GLDA concentration of 40%) was sprayed onto the cut hydrogel polymer and mixed by chopping (hole size: 16 mm). At this time, 0.5 parts by weight of GLDA was mixed relative to 100 parts by weight of the base resin.
[0272] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0273] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0274] 0.3 parts by weight of the mixture A in an aqueous solution was mixed with the surface-treated super absorbent polymer relative to 100 parts by weight of the base resin. Then, a drying step was performed at 80° C. for 25 minutes.
[0275] Example 12
[0276] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0277] The prepared hydrogel polymer was in the form of a sheet, and the sheet was cut into small pieces. A GLDA aqueous solution (GLDA concentration of 40%) was sprayed onto the cut hydrogel polymer and mixed by chopping (hole size: 16 mm). At this time, 0.5 parts by weight of GLDA was mixed relative to 100 parts by weight of the base resin.
[0278] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0279] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0280] 0.3 parts by weight of the mixture A in an aqueous solution was mixed with the surface-treated super absorbent polymer relative to 100 parts by weight of the base resin. Then, a drying step was performed at 80° C. for 25 minutes.
[0281] Example 13
[0282] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0283] The prepared hydrogel polymer was in the form of a sheet, and the sheet was cut into small pieces. An EDTA aqueous solution (EDTA concentration of 40%) was sprayed onto the cut hydrogel polymer and mixed by chopping (hole size: 16 mm). At this time, 0.5 parts by weight of EDTA was mixed relative to 100 parts by weight of the base resin.
[0284] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0285] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0286] Mixture A was mixed with iodine aqueous solution I2 and CuI (each with a concentration of 1%) and the surface-treated superabsorbent polymer. At this time, 0.3 weight parts of mixture A in aqueous solution were mixed with respect to 100 weight parts of base resin, and 1.0 weight parts of iodine aqueous solution were mixed with respect to 100 weight parts of base resin. Then, a drying step was performed at 80° C. for 25 minutes.
[0287] Embodiment 14
[0288] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of sodium hydroxide (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was added to the supply part of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated using a UV irradiation device (irradiation amount: 10 mW / cm 2 ) was irradiated with ultraviolet rays while maintaining the polymerization temperature at 80° C. for 2 minutes to perform UV polymerization, thereby preparing a hydrogel polymer.
[0289] The prepared hydrogel polymer was in the form of a sheet, and the sheet was cut into small pieces. An EDTA aqueous solution (EDTA concentration of 40%) was sprayed onto the cut hydrogel polymer and mixed by chopping (hole size: 16 mm). At this time, 0.5 parts by weight of EDTA was mixed relative to 100 parts by weight of the base resin.
[0290] The prepared hydrogel polymer was transferred to a meat grinder and cut into 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at a temperature of 170° C. for 30 minutes, and the dried hydrogel polymer was pulverized with a pin mill. Subsequently, a base resin was prepared by classifying the polymer with a particle size of 150 μm to 850 μm using a sieve.
[0291] After that, 100 parts by weight of the above-prepared base resin was uniformly mixed with a surface crosslinking solution (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate octahydrate (Al-S) and 0.1 parts by weight of silica (Aerosil A200)), and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0292] Mixture A and citric acid were mixed with the surface treated super absorbent polymer. At this time, 0.3 parts by weight of mixture A in an aqueous solution was mixed with respect to 100 parts by weight of the base resin, and 1.0 parts by weight of citric acid in an aqueous solution (concentration of 1%) was mixed with respect to 100 parts by weight of the base resin. Then, a drying step was performed at 80° C. for 25 minutes.
[0293] Table 1
[0294]
[0295]
[0296]
[0297] Experimental example
[0298] The physical properties of the superabsorbent polymer compositions prepared in Examples and Comparative Examples were measured by the following methods.
[0299] 1) Bacterial growth inhibition rate
[0300] 50 ml of synthetic urine inoculated with 3000 CFU / ml of Escherichia coli was added to 2 g of the superabsorbent polymer of Comparative Example 1, and then incubated in an incubator at 35° C. for 12 hours. The incubated sample was washed with 150 mL of saline (0.9 wt % sodium chloride aqueous solution) and incubated on a nutrient broth agar (BDDIFCO.) plate to measure CFU (colony forming unit; CFU / ml) of physical properties as a control group.
[0301] 50 ml of synthetic urine inoculated with 3000 CFU / ml Escherichia coli was added to 2 g of the superabsorbent polymer prepared in each of the examples and comparative examples, and then incubated in an incubator at 35° C. for 12 hours. 150 mL of saline (0.9 wt % sodium chloride aqueous solution) was added to the incubated sample and shaken for 1 minute to mix evenly. The resulting diluted solution was spread on a nutrient broth agar (BDDIFCO.) plate and incubated in an incubator at 30° C. for 24 hours to measure CFU (colony forming unit; CFU / ml).
[0302] The bacterial growth inhibition rate defined by the following Equation 1 was calculated using these measurement results, and the antibacterial activity of each super absorbent polymer of Examples and Comparative Examples was evaluated.
[0303] [Equation 1]
[0304] Bacterial growth inhibition rate = [1-{CFU (12 hours) / CFU control (12 hours)}] × 100 (%)
[0305] In equation 1,
[0306] CFU (12 hours) means the number of proliferating bacterial individuals per unit volume of synthetic urine (CFU / ml), which is obtained by adding a superabsorbent polymer to synthetic urine inoculated with Escherichia coli bacteria and then incubating at 35°C for 12 hours, and
[0307] The CFU control (12 hours) represents the number of proliferating bacterial individuals per unit volume of synthetic urine (CFU / ml), which is obtained by inoculating the above-mentioned bacteria on the superabsorbent polymer of Comparative Example 1 under the same conditions to cultivate synthetic urine, and represents the number of bacterial individuals per unit volume of synthetic urine (CFU / ml) measured for the control group.
[0308] 2) Deodorization ability
[0309] The deodorizing ability was measured using an adsorption chamber test method. 3-Methylbutyraldehyde was selected as the aldehyde odorant and dimethyl trisulfide (DMTS) was selected as the sulfur compound odorant.
[0310] -Adsorption chamber measurement method: 1g of superabsorbent polymer was added to a 500mL glass bottle, and then 25mL of odorous substances were injected. Then, aging was performed in a constant temperature chamber for 3 hours, and then collection was performed for 20 minutes. The temperature of the constant temperature chamber at this time was 35°C, and the N2 flow rate was 250mL / min. The extruded odor was then adsorbed into the connected adsorption chamber, and collected after repeating the same operation twice for the same sample. The collected results were analyzed by GC to confirm the results.
[0311] - Deodorizing ability (%) = (the amount of odor of the reference sample (superabsorbent polymer of Comparative Example 1) measured by GC - the amount of odor of the sample measured by GC) / the amount of odor of the reference sample (superabsorbent polymer of Comparative Example 1) measured by GC × 100 (%)
[0312] 3) Centrifugal Retention Capacity (CRC)
[0313] The centrifuge retention capacity of each superabsorbent polymer is measured by the absorption ratio under no-load conditions according to EDANA (European Disposables and Nonwovens Association, EDANA) WSP241.3.
[0314] Specifically, the polymer obtained from the embodiment and the comparative example is obtained to obtain a polymer having a particle size of 300 to 600 μm. After W0 (g, about 0.2 g) polymer is uniformly inserted into the nonwoven fabric envelope and sealed, it is soaked in physiological saline (0.9 wt % sodium chloride aqueous solution) at room temperature. After 30 minutes, the envelope is centrifuged at 250G for 3 minutes to drain water, and the weight W2 (g) of the envelope is measured. In addition, after the same operation is performed without using the polymer, the weight W1 (g) of the envelope is measured.
[0315] Then, the CRC (g / g) was calculated using the obtained weight value according to the following calculation equation 1.
[0316] [Calculation equation 1]
[0317] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}–1
[0318] 4) Absorption under pressure (AUP)
[0319] The pressure absorption rates of the super absorbent polymers prepared in Examples and Comparative Examples at 0.7 psi were measured according to EDA NAWSP 242.3.
[0320] First, the fractionated polymers used for the above-mentioned CRC measurements were used in the AUP measurements.
[0321] Specifically, a 400-mesh stainless steel screen is installed in the cylindrical bottom of a plastic with an inner diameter of 25 mm. W0 (g) of superabsorbent polymer is evenly dispersed on the screen at room temperature and 50% humidity. After that, a piston capable of evenly providing a 0.7 psi load is placed thereon. Among them, the outer diameter of the piston is slightly less than 25 mm, there is no gap with the inner wall of the cylinder, and the piston movement (jig-jog) of the cylinder is uninterrupted. At this time, the weight of the measuring device is W3 (g).
[0322] Subsequently, a glass filter with a diameter of 90 mm and a thickness of 5 mm is placed in a culture dish with a diameter of 150 mm, and salt water (0.9 wt % sodium chloride) is poured into the culture dish. At this time, the salt water is poured until the surface of the salt water is level with the upper surface of the glass filter. A filter paper with a diameter of 90 mm is placed on it. After placing the measuring device on the filter paper, absorb the liquid under load for 1 hour. After 1 hour, lift the measuring device and measure the weight W4 (g). Then, according to the following calculation equation 2, the obtained mass value is used to calculate the pressurized absorption rate (g / g).
[0323] [Calculation equation 2]
[0324] AUP(g / g)=[W4(g)–W3(g)] / W0(g)
[0325] The experimental results are shown in Table 2.
[0326] Table 2
[0327]
[0328] According to the results in Table 2, Examples showed excellent bacterial growth inhibition rate and deodorizing ability while maintaining absorbency at a level similar to that of Comparative Example 1 containing no additive.
[0329] In addition, in the case of Comparative Example 2 using only a chelating agent without a deodorant, the bacterial growth inhibition rate was at a similar level, but the deodorizing ability was very poor. Comparative Examples 3, 6, and 7 using only a deodorant without a chelating agent did not inhibit bacteria at all, and their deodorizing abilities tended to be lower than those of the Examples.
[0330] Unlike the Examples, Comparative Example 4 using methionine instead of glycine did not show an excellent deodorizing effect on both aldehydes and sulfur compounds at the same time.
[0331] In the case of Comparative Example 5 containing a chelating agent and glycine but not containing a persimmon extract, it was confirmed that the deodorizing ability for both aldehyde-based substances and sulfur compound-based substances was inferior to that of Examples.
Claims
1. A superabsorbent polymer composition comprising: A superabsorbent polymer comprising a base resin containing a cross-linked polymer cross-linked and polymerized by an acrylic monomer having an acidic group at least partially neutralized and an internal cross-linking agent, and a surface cross-linked layer formed by further cross-linking the cross-linked polymer using a surface cross-linking agent on the surface of the base resin; Persimmon extract; Glycine; and Chelating agent. 2 . The superabsorbent polymer composition according to claim 1 , wherein the persimmon extract is contained in an amount of 0.005 to 0.050 parts by weight in terms of solid content relative to 100 parts by weight of the base resin. 3 . The superabsorbent polymer composition of claim 1 , wherein the glycine is included in an amount of 0.005 to 0.050 parts by weight relative to 100 parts by weight of the base resin. 4 . The super absorbent polymer composition of claim 1 , wherein the glycine is contained in an amount of 100 to 200 parts by weight relative to 100 parts by weight of the persimmon extract in terms of solid content. 5 . The superabsorbent polymer composition of claim 1 , wherein the chelating agent is included in an amount of 0.1 to 2.0 parts by weight relative to 100 parts by weight of the base resin.
6. The superabsorbent polymer composition of claim 1, wherein the superabsorbent polymer composition further comprises one or more additives selected from the group consisting of organic acids, iodine compounds, glycerin, and zinc chloride.
7. The superabsorbent polymer composition of claim 1, wherein the chelating agent comprises a glycine-based chelating agent.
8. The superabsorbent polymer composition of claim 7, wherein the aminoacetic acid-based chelating agent comprises at least one selected from the group consisting of ethylenediaminetetraacetic acid (EDTA), L-glutamic acid diacetic acid (GLDA), methylglycine diacetic acid (MGDA), hydroxyethylethylenediaminetriacetic acid (HEDTA), ethanol diglycine (EDG), diethylenetriaminepentaacetic acid (DTPA) and salts thereof.
9. The superabsorbent polymer composition of claim 1, wherein the persimmon extract, glycine, and a chelating agent are each independently contained in the base resin or in the surface cross-linking layer.
10. A method for preparing a superabsorbent polymer composition, comprising the following steps: Step 1: forming a hydrogel polymer by cross-linking and polymerizing an acrylic monomer having at least partially neutralized acidic groups in the presence of an internal cross-linking agent and a polymerization initiator; Step 2: preparing a base resin containing a cross-linked polymer obtained by drying and pulverizing the hydrogel polymer; Step 3: preparing a mixture by mixing a surface cross-linking solution with the base resin; and Step 4: preparing a super absorbent polymer having a surface cross-linked layer formed on the surface of the base resin by heat-treating the mixture; wherein the mixture containing the persimmon extract and glycine is mixed with the surface cross-linking solution of step 3, or is mixed with the super absorbent polymer having a surface cross-linking layer formed thereon in step 4, and The chelating agent is mixed with the hydrogel polymer of step 1, or with the surface cross-linking solution of step 3, or with the superabsorbent polymer having a surface cross-linking layer formed thereon of step 4.
11. The method for preparing a super absorbent polymer composition according to claim 10, wherein the mixing amount of the persimmon extract is 0.005 to 0.050 parts by weight in terms of solid content relative to 100 parts by weight of the base resin. 12 . The method for preparing a super absorbent polymer composition according to claim 10 , wherein the mixing amount of the glycine is 0.005 to 0.050 parts by weight relative to 100 parts by weight of the base resin. 13 . The method for preparing a super absorbent polymer composition according to claim 10 , wherein the content of the glycine is 100 to 200 parts by weight relative to 100 parts by weight of the persimmon extract in terms of solid content.
14. The method for preparing a super absorbent polymer composition according to claim 10, wherein the mixing amount of the chelating agent is 0.1 to 2.0 parts by weight relative to 100 parts by weight of the base resin.
15. The method for preparing a superabsorbent polymer composition according to claim 10, further comprising, after step 4, step 5: mixing one or more additives selected from the group consisting of organic acids, iodine compounds, glycerol and zinc chloride with the superabsorbent polymer having a surface crosslinked layer formed thereon.
16. The method for preparing a superabsorbent polymer composition according to claim 10, wherein the chelating agent comprises a aminoacetic acid-based chelating agent.
17. The method for preparing a superabsorbent polymer composition according to claim 16, wherein the aminoacetic acid-based chelating agent comprises at least one selected from the group consisting of ethylenediaminetetraacetic acid (EDTA), L-glutamic acid diacetic acid (GLDA), methylglycine diacetic acid (MGDA), hydroxyethylethylenediaminetriacetic acid (HEDTA), ethanol diglycine (EDG), diethylenetriaminepentaacetic acid (DTPA) and salts thereof.
Citation Information
Patent Citations
resin composition
KR1020230164000A